Quantitative ethnomedicinal investigation of medicinal plants used by traditional healers to treat various diseases in the district Dindori, Madhya Pradesh, India - Ahirwar, Ramesh Kumar; Gupta, Vivek (Ethnobotany Research and Applications, 2024)
Background: Despite the wisdom of using medicinal plants for various diseases therapies by practitioners of Ayurveda and traditional medicine, the process of documenting this knowledge is untapped to date. The aim of the present study was to record the knowledge and utility of medicinal plants used as remedies for various diseases by traditional healers in Dindori, Madhya Pradesh. Methods: Field surveys were conducted from January 2018 to December 2019 to collect ethnomedicinal data through semi-structured interviews and group discussions by using standard questionnaire. Reported data was analyzed using various ethnobotanical indices. All collected plant specimens were deposited in the Herbarium of Department of Botany, Guru Ghasidas Vishwavidyalaya, Bilaspur, Chhattisgarh for future reference. Results: A total of 88 plant species belonging to 80 genera in 46 families were reported during current study and were used for the treatment of 65 different diseases categorized into 14 ailment categories. The highest ICF of 1.0 was noted for gynecological disorders, hair care and male infertility problem. Cynodon dactylon recorded highest UV and FL of 33.33 to 100%, respectively. Among plant parts, Leaves (40.33%) were most commonly used by traditional healers. Conclusions: Traditional knowledge of plants was only passed on by passing of information from person to person using oral communication is on the verge of extinction. Hence, the medicinal plants and traditional treasures associated with it must be documented. The species reported with high use value (UV) and fidelity level value (FL) should be explored for further phytochemical and pharmacological investigation to authenticate this indigenous knowledge. Keywords: Quantitative ethnobotany, Ethnomedicinal plants, Traditional healers, Dindori, Madhya Pradesh